Reduced delays in A&E for elderly patients with hip fractures. - Charalambous, C. P. (2003)
Published guidelines recommend early transfer of patients with hip fractures to hospital wards and avoidance of unnecessary delays in A&E. We describe a protocol whereby the liaison of an orthopaedic trauma co-ordinator with A&E reduced A&E-to-ward transfer times by 43%. Following introduction of the new protocol, 39% of hip fracture patients were in a ward bed within 3 h of admission to A&E compared to 4% previously. The new protocol also reduces administrative workload for the on-call orthopaedic SHOs.